Dynamics of Revenues of Enterprises in Foreign Ownership at Russian Automotive Industry - Spitsin V. V. Vladislav Vladimirovich; Mikhalchuk A. A. Aleksandr Alexandrovich; Trifonov A. Yu. Andrey Yurievich; Gumennikov I. V. Iliya Vladimirovich; Bulykina A. Anastasia (2017, 2017)
Title screen